Job burnout among workers with different shift regularity: interactive factors between sleep, depression, and work environment - Gu, Hyerin; Lee, Jooyoung; Hwang, Yunjee; Kim, Jichul; Lee, Somi; Kim, Seog Ju (Frontiers in Public Health, 2023)
Object We investigated burnout and associated factors in non-shift workers (NSWs), shift workers with regular rotating shifts (RRSWs), and shift workers with irregular or unpredictable rotating shifts (IRSWs). Methods In total, 5,125 adult workers (1,966 NSWs, 1,936 RRSWs, and 1,223 IRSWs) participated in an online self-reported survey. Job burnout and three dimensions thereof (exhaustion, cynicism, and professional efficacy) were assessed using the Maslach Burnout Inventory—General Survey (MBI-GS). The Center for Epidemiological Studies Depression Scale (CES-D) (depressive symptoms), Pittsburgh Sleep Quality Index (PSQI) (subjective sleep quality), and Korean Occupational Stress Scale (KOSS) (stressful job environment) were also used. Results Both types of shift workers scored higher in terms of exhaustion, cynicism, and poor professional efficacy on the MBI-GS compared with NSWs after controlling for age and gender. IRSWs exhibited higher scores on the exhaustion and professional efficacy dimensions of the MBI-GS compared with RRSWs. After controlling for the CES-D and PSQI scores, we found no significant difference in cynicism among the groups. After controlling for the KOSS score, we found no significant difference in professional efficacy. All MBI-GS dimensional scores were correlated significantly with the CES-D, PSQI, and KOSS scores in all three groups. Conclusion The job burnout level of rotating shift workers, especially those with irregular shifts, was higher than that of other workers. Cynicism in shift workers may be largely attributable to poor sleep or depression; the poor efficacy of shift workers may be explained by their stressful work environment.